Autophagy regulation using luteolin: new insight into its anti-tumor activity - Milad Ashrafizadeh; Zahra Ahmadi; Tahereh Farkhondeh; Saeed Samarghandian (Cancer Cell International, 2020)
Abstract Application of novel methods in cancer therapy is important in terms of management and treatment of the life-threatening disorder. It appears that autophagy is a potential target in cancer therapy, as a variety of drugs targeting autophagy have shown great potential in reducing the viability and proliferation of cancer cells. Autophagy is primarily a catabolic process which provides energy during starvation. Besides, this process contributes to the degradation of aged or potentially toxic components and organelles. On the other hand, the source of a variety of naturally occurring anti-tumor drugs are flavonoids which have high anti-tumor activity. Luteolin is a polyphenolic flavone with the great pharmacological effects such as anti-diabetic, hepatoprotective, antioxidant, anti-inflammation, and anti-tumor. At the present review, we demonstrate how luteolin affects on autophagy process to induce anti-tumor activity.